An investigation on Dimensions, Mechanical Properties, and Microstructure of the Carbon Steel Wall using MIG/MAG Welding as a WAAM Process - S.M.A. Tabatabaei Majd; J. Rasti; H.R. Ghazvinloo (Journal of Advanced Materials in Engineering)
The purpose of this paper is to investigate the manufacturing of a steel wall using gas metal arc welding (GMAW) process and to study its dimensional features, mechanical properties, and the microstructure. The selected parameters were the interpass dwell time, the welding speed, and the wire feeding speed. Based on the results, the average wall height and thickness decreases with increasing welding speed due to less weld deposition in the layer. A relationship between the wall thickness and height in terms of the welding speed and wire feeding speed was proposed. A longer interpass dwell time increased the wall height. The effective area percentage also increased with increasing welding speed. Tensile strength and elongation (%) were investigated based on the presence or absence of voids and microstructure. In high welding speed and long interpass dwell time, the microstructure included columnar grains with fine widmanstätten ferrite and intergranular pearlite. At low welding speed and short interpass dwell time, the microstructure consisted mostly of blocky ferrite and coarse pearlite. Both of these structures showed satisfactory strength and elongation. But in the other conditions, where the possibility of brittle phases in the heat-affected zone was higher, the strength and elongation decreased.